Host status and disease threshold of Rhizoctonia solani and Fusarium solani on Salvia hispanica L. and its suitability as a rotational crop to Nicotiana tabacum L. - Chofamba, Anyway (Journal of Scientific Agriculture, 2020)
The study was done following the continued outbreaks of problematic diseases in the production of tobacco (Nicotiana tabacum L.) in Zimbabwe which amongst the problematic ones are Rhizoctonia solani and Fusarium solani. The experiment was conducted at Marondera University of Agriculture Science and Technology in Zimbabwe, aiming to evaluate the suitability of Chia as a rotational crop to tobacco. Chia is a seed oil producing legume crop which is regarded the most suitable in rotation with tobacco at the moment because of its monetary benefit to the farmer hence will encourage crop rotation. An experiment was set up with two trials in three growing seasons arranged in a complete block design. Fusarium solani five treatments were used one control and four other different rates of inoculum 2.5g,3.5g, 5.5g and 7.5g/10ml of Distilled water and Rhizoctonia solani five treatments were used with a control and four other different inoculations rates inoculated at 0.1g, 0.2g, 0.4g and 0.6g/10ml Distilled water. Data collection was based on the disease severity scale and index of Chia, and also histochemical parameters which were hydrogen peroxide content and malonaldehyde content. There was significant (p < 0.05) differences between the different inoculation rates of all the measured parameters under the distinct diseases. Hence Chia cannot be rotated with tobacco even under low levels of disease threshold within the soil, unless proper and intensive management practices are put in place.